1965
DOI: 10.1071/ar9650189
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive performance of Merino ewes grazing red clover (Trifolium pratense L.), improved pasture, or native pasture

Abstract: Each year, commencing in 1957, fine-wool Merino ewes that were born in 1954 grazed native and improved pasture from the time of weaning of their lambs (usually late January) until the end of the period when they were joined with rams (early June). For the remainder of each year, one group each grazed (A) improved pasture, (B) native pasture, and (C) a red clover (Trifolium pratense) pasture. Records of services, lambings, and birth and weaning weights of lambs were obtained each year until the final weaning in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

1975
1975
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 0 publications
0
11
1
Order By: Relevance
“…In contrast, we found that grazing red clover did not affect the incidence of oestrus over the mating period, a finding supported by Newton & Betts (1973). Barrett et al (1965), using the opposite grazing regime to ours (i.e. ewes grazed red clover pasture during pregnancy and lactation), did not record any differences in conception to first service, but did note an increase in barrenness.…”
Section: Discussioncontrasting
confidence: 73%
“…In contrast, we found that grazing red clover did not affect the incidence of oestrus over the mating period, a finding supported by Newton & Betts (1973). Barrett et al (1965), using the opposite grazing regime to ours (i.e. ewes grazed red clover pasture during pregnancy and lactation), did not record any differences in conception to first service, but did note an increase in barrenness.…”
Section: Discussioncontrasting
confidence: 73%
“…When grazed at or about mating, conception rates and ovulation rates (or lambs born per ewe lambing) are decreased (Morley et al 1964;Newton & Betts 1973;Lightfoot & Wroth 1974). Permanent and progressive infertility occurs when formononetin-rich pastures are grazed for prolonged periods at any time of the year (Barrett et al 1965;Davenport 1967;Davies & Maller 1970). There is also some evidence to suggest that if ewe lambs graze oestrogenic clovers, their subsequent fertility may be affected (Underwood & Shier 1951;Marshall 1973), although Ch 'ang (1961 found no carryover effects.…”
Section: Haymentioning
confidence: 99%
“…Long-term grazing of oestrogenic clover pastures may cause permanent infertility in ewes (Bennetts et al 1946;Barrett et al 1965) although not all ewes grazing oestrogenic clover exhibit infertility. Infertile ewes have uterine endometrial hyperplasia and changes in cell type and function of the cervix (Adams 1976).…”
Section: Introductionmentioning
confidence: 99%